ANALISIS TINGKAT KESEHATAN BANK MENGGUNAKAN METODE REGC PADA BANK UMUM SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2020 - Fitriani Fitriani; Nurul Susianti; Kurniawati Meylianingrum; Siti Nur Annisa Amalia (UIN Mataram, 2022)
This study aims to determine the soundness of Islamic Commercial Banks listed on theIndonesia Stock Exchange for the period 2018-2020 using the REGC method Risk profile(Risk profile), Good Corporate Governance (GCG), Profitability (Earnings) and Capital(Capital). This study uses a quantitative descriptive approach with the research subject ofIslamic Commercial Banks listed on the Indonesia Stock Exchange for the 2018-2020 period.The data were obtained by using literature study and documentation techniques. The dataanalysis technique used in this study is financial analysis using the RGEC method The resultsof the study show that the performance of each Islamic Commercial Bank is in the samecomposite rank each year, namely: BRI Syariah Bank for the 2018-2020 period is at compositerank 2 (PK-2) with the HEALTHY category according to the details of the weight of thedetermination composite ratings are 74.29%, 82.86% and 82.86. Panin Dubai Syariah Bank forthe 2018-2020 period is at composite rank 3 (PK-3) with the ENOUGH HEALTHY categoryaccording to the weighting of the composite ratings of 65.71%, 62.86% and 62.86.Furthermore, BTPN Syariah is ranked composite 1 (PK-1) with the VERY HEALTHYcategory according to the weight of the composite rating of 91.43% in a row during the 2018-2020 period.